Pengaruh Intellectual Capital Terhadap Nilai Pasar Perusahaan Otomotif Yang Terdaftar DI BEI 2007-2011 - Nurani, Nadiah Candra; ', Zulbahridar; ', Azhari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to invetegate the effect of variables physical capital (VACA), Human Capital (VAHU), and Structural Capital (STVA) on market to book value in otomotif companies in the period 2007-2011on Indonesia Stock Exchange. The data is sampled using purposive sample judgment method. Totally, there are 17 listed companies which are selected using purposive sampling method. This research is analized by multiple regression analysis, using SPSS program. The results of this research indicate that physical capital (VACA) has no significant effect on market to book value. In contrast, human capital (VAHU) and structural capital (STVA) has significant effect on market to book value during 2007-2011.Keywords : Intellectual Capital, Market Value